استخدام الطريقة السمعية الشفهية لترقية مهارة الكلام في الصف الحادية عشر بالمدرسة الثانوية دار الفائزين موجووارنو جومبانج: Penggunaan Metode Dengar-Ucap untuk Meningkatkan Keterampilan Berbicara Kelas 11 Madrasah Aliyah Darul Faizin, Mojowarno, Jombang - Sukiman; Abidin, Hasan (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2024)
Learning speaking skills must be given to students in the initial stages of learning a second (foreign) language, including learning Arabic. Even though speaking skills occupy a very important position, researchers through interviews with Arabic language teachers in Class XI-IPS1 found that most Class This fact is also confirmed by the Arabic oral test scores which are below the minimum completion limit in the field of Arabic language studies. The results of the research show that the application of the Audio-lingual method has proven to be effective in improving the speaking skills of Class The quantitative evidence is the results of the oral tests for all students which show that all groups obtained scores in the passing range, meaning that they exceeded the minimum standard for completeness in Arabic lessons, namely 6.5, the minimum score obtained by all students was 69.2. As for the aspect of the speaking proficiency test in the form of pronunciation, a score of 79.2 was obtained, meaning that this method has a great influence on increasing proficiency and fluency in Arabic.